A Wolf 359 in sheep's clothing: hunting for substellar companions in the fifth-closest system using combined high-contrast imaging and radial velocity analysis - Bowens-Rubin, Rachel; Murphy, Joseph M. Akana; Hinz, Philip M.; Limbach, Mary Anne; Seifahrt, Andreas; Kiman, Rocio; Salama, Maïssa; Mukherjee, Sagnick; Brady, Madison; Carter, Aarynn L.; Jensen-Clem, Rebecca; Kooten, Maaike A. M. van; et al. (The astronomical journal, 2023)
Wolf 359 (CN Leo, GJ 406, Gaia DR3 3864972938605115520) is a low-mass star in the fifth-closest neighboring system (2.41 pc). Because of its relative youth and proximity, Wolf 359 offers a unique opportunity to study substellar companions around M stars using infrared high-contrast imaging and radial velocity monitoring. We present the results of Ms-band (4.67 μm) vector vortex coronagraphic imaging using Keck-NIRC2 and add 12 Keck-HIRES and 68 MAROON-X velocities to the radial velocity baseline. Our analysis incorporates these data alongside literature radial velocities from CARMENES, the High Accuracy Radial velocity Planet Searcher, and Keck-HIRES to rule out the existence of a close (a < 10 au) stellar or brown dwarf companion and the majority of large gas giant companions. Our survey does not refute or confirm the long-period radial velocity candidate, Wolf 359 b (P ∼ 2900 days), but rules out the candidate's existence as a large gas giant (>4 M Jup) assuming an age of younger than 1 Gyr. We discuss the performance of our high-contrast imaging survey to aid future observers using Keck-NIRC2 in conjunction with the vortex coronagraph in the Ms band and conclude by exploring the direct imaging capabilities with JWST to observe Jupiter- and Neptune-mass planets around Wolf 359.
Gesehen am 26.01.2024